1,3,4,6-Tetrachloro-7,7-bis(4-chlorophenyl)bicyclo[4.2.0]oct-3-ene-2,5-dione - Huayou Hu; Lei Li; Jun-Feng Ji; Zhi-Guo Shen (Acta Crystallographica Section E, 2008)
The title compound, C20H10Cl6O2, a quinone derivative, was obtained by the irradiation of 2,3,5,6-tetrachlorobenzoquinone and 4,4′-(ethene-1,1-diyl)bis(chlorobenzene). The six- and four-membered rings are fused in a cis configuration. The dihedral angle between them is 53.4 (3)°.